Role of Police in Respecting Crimes on Prisoners Who Get Asimilation & Conditioned Delivery Due to Plague of Covid-19 - Lilik Purwoko; Siti Rodhiyah Dwi Istinah (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2020)
The purpose of this study was to determine and analyze the role of the Police in tackling crimes by convicts who received assimilation and parole due to the Covid-19 virus outbreak and the obstacles and solutions of the Police in overcoming crimes by inmates who received assimilation and parole due to the Covid-19 virus outbreak. Used in this research is an empirical juridical approach. This type of research is descriptive analytical, data collection methods used are primary data (interviews) and secondary data (literature review). The data analysis was done qualitatively. The results of the research found that the role of the Police in tackling crimes by inmates who received assimilation and parole due to the Covid-19 virus outbreak has an important role. Which was carried out by the Police in minimizing crimes committed by inmates who received assimilation due to the impact of Covid-19, namely preventive efforts to conduct patrols by forming a new eagle team, as well as repressive efforts to provide strict punishment to inmates who committed crimes again after assimilation. The obstacles faced by the Police in overcoming crimes by inmates who receive assimilation and parole due to the Covid-19 virus outbreak include, among others, that not all criminals are domiciled in the city of Semarang, the number of personnel is not proportional to the number of prisoners who receive assimilation and parole due to the virus outbreak. Covid-19, the National Police and the Police have never received a copy of the trial verdict from the court.